Karakteristik Kimia Tanah pada Areal Kelapa Sawit dan Nilai Konservasi Tinggi (NKT) di Kabupaten Tapin, Provinsi Kalimantan Selatan - Muhammad Haykal Fiqri; Abdul Haris; Abdul Hadi (Acta Solum, 2023)
In the practice of oil palm plantation management, land clearing and cultivation using heavy equipment will change soil conditions from anaerobic to aerobic. This condition will cause sulfide compounds contained in the soil, or commonly referred to as pyrite (FeS2) to undergo an oxidation process that can cause the formation of sulfuric acid compounds (H2SO4) which when dissociated will release H+ ions in the soil solution, thus increasing soil acidity. In addition, improved drainage will also lead to a high likelihood of plant nutrients being leached from the soil. On the other hand, the HCV areas will be left unmanaged by maintaining the original vegetation adjacent to the oil palm plantations. So there are two different land management systems between oil palm land and HCV areas which in theory will have different land characteristics, one of which can be seen from differences in soil chemical characteristics. The purpose of this study was to determine the differences in the characteristics of several soil chemical properties including pH, C-organic, Al-dd and P-available in oil palm land and HCV areas. This research is a field research using survey method. Sampling in the field was carried out by purposive sampling at PT Kharisma Inti Usaha, Tapin Regency, South Kalimantan Province. Soil samples used in this study were soil samples at a depth of 0-30 cm and 30-60 cm on oil palm land and HCV areas where each land was taken as many as 10 sampling points, so that the total sample points amounted to 40 sampling points. The results showed that the characteristics of soil acidity (pH), carbon (C-organic), aluminum (Al-dd) and phosphorus (P-available) on oil palm land were lower than HCV areas in PT Kharisma Inti Usaha Tapin Regency.